Role of the spindle pole body of yeast in mediating assembly of the prospore membrane during meiosis - Knop, Michael; Strasser, Katrin (The EMBO journal, 2000)
Spindle pole bodies (SPBs) are the centrosome equivalents in yeast, required for microtubule organization. In yeast, the SPB further serves as the attachment sites of the prospore membrane during meiosis. Here we report the identification of two new meiosis-specific components of the SPB, Mpc54p and Mpc70p, and the first protein specific for the prospore membrane, Don1p. Mpc54p and Mpc70p are not present in mitotic SPBs, and during meiosis II they are components of a meiosis-specific structural alteration of the outer plaque of the SPB. Both proteins are dispensable for the meiotic divisions but are essentially required for the formation of the prospore membrane. In the mpc54 and mpc70 mutants, the Don1p-containing precursors of the prospore membrane can still be found in the cytoplasm and associated with the SPB. Unexpectedly, however, the assembly of the precursors to a continuous membrane system is affected. Thus, the meiotic SPB is directly involved in the formation of a specialized membrane system, the membrane of the prospore.